Alimentação e dados sociodemográficos de adultos com diabetes mellitus tipo 1 durante o distanciamento social da covid-19 - BRASIL, Heloisy Andrea da Costa (2023)
Introduction: After the WHO declared a COVID19 pandemic, social distancing was widely recommended to control the spread of the coronavirus. Individuals with Diabetes Mellitus are part of the risk group for the disease. Sociodemographic factors have an impact on the treatment and food choices of people with Type 1 Diabetes Mellitus (T1DM), as well as on the risk of contracting the coronavirus. Objective: to evaluate the association between eating habits and sociodemographic factors of adults with DM1 during social distance by COVID19. Objective: To evaluate the association between eating habits and sociodemographic factors of adults with Type 1 Diabetes Mellitus (T1DM) in the context of social distancing by COVID19. Methods: Crosssectional, descriptive and analytical study, carried out in July 2020, using a form on the Google® Forms platform. Sociodemographic data, information on social distance and food choices were collected. For statistical analysis, the Chisquare test was performed, considering p <0.05. Results: An association was observed between social distancing and being female (p=0,014), living with individuals with diabetes (p=0,037) and having income maintained during the pandemic (p=0,032). Being female was associated with increasing the consumption of snacks (p=0,003) and sweets (p=0,016). Being between 18 and 24 years old was associated with changing food consumption (p=0,001) and increasing food consumption (p=0,001), especially for snacks (p=0,005). Being over 45 years old associated with maintaining the dietary pattern during this period (p=0,001). Having income maintained or increased during the pandemic was associated with maintaining the dietary pattern (p=0,042). Conclusion: Age group, sex and income can influence the eating habits of adults with DM1 during social distance, which warns of the need to maintain nutritional assistance during this period in order to guarantee a healthy eating pattern, as well as having minimum income guarantee programs to ensure access to good quality food.